Learning community eTwinning: a literature review - Gökhan Şahin; Hasan Gökçe; Hilal Karabulut; İshak Afşin Kariper (Springer, 2024)
Abstract This study aims to reveal the general trend by examining the publications made between 2007 and 2023 related to eTwinning under various themes. Meta-synthesis method, a qualitative research design, was employed in this study. It is aimed to reveal the big picture for eTwining. eTwining is a newer education platform. A few study is seen and no review article is published in the literature. The results are presented as frequency and percentages. The review revealed that the highest number of studies was carried out in 2021, and qualitative research was the most preferred method. In addition, the studies were primarily performed with teachers and students, and the most used data collection tool was the interview. Teacher opinions and language education were the most common subjects in publications. Based on these results, it was suggested to employ quantitative and mixed methods and include different sample groups in future research.